The relationship between echocardiographic parameters and brain natriuretic peptide levels in acute and chronic mitral regurgitation - Kargin, Ramazan (Türk Kardiyoloji Derneği arşivi, 2011)
Plasma brain natriuretic peptide (BNP) level increases with symptoms and severity of mitral regurgitation (MR). We aimed to determine the relationship between plasma BNP levels and echocardiographic parameters in patients with acute and chronic MR. The study included 55 patients (31 males, 24 females) with isolated moderate-to-severe MR. Of these, 31 patients had acute MR, and 24 patients had chronic MR. All the patients were assessed by transthoracic, transesophageal and Doppler echocardiography and plasma BNP levels were determined. Clinical characteristics and functional capacity were similar in the two groups. Patients with acute MR had significantly higher left ventricular (LV) ejection fraction (EF) (p=0.001), and significantly lower LV end-systolic diameter (p=0.016), end-systolic volume (p=0.027), end-diastolic diameter (p=0.011), left atrial volume (LAV) (p=0.003), and plasma BNP levels (p=0.036). Effective regurgitation orifice area was also significantly higher in patients with acute MR (p=0.038). In multiple linear regression analysis, the natural logarithm of BNP was significantly correlated with E/Ea ratio (β=0.50, p=0.002) and LAV (β=0.38, p=0.015) in patients with acute MR, and with systolic pulmonary artery pressure (β=0.60, p=0.002) and EF (β=-0.36, p=0.039) in patients with chronic MR. Although the echocardiographic degree of MR was more pronounced in patients with acute MR, serum BNP levels tended to be lower in this group. Correlation of serum BNP with E/Ea and LAV in this group may be an important finding.